Isoterm, Termodinamika Dan Kinetika Adsorpsi Logam Cu Menggunakan Adsorben Serbuk Kulit Udang - Hadi Ikrima; Yelmida A; Syamsu Herman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Most of the shrimp shell waste consists of chitin compounds which can be converted into chitosan. The use of chitin and chitosan are mainly as chelating agents, emulsifiers and adsorbents. In this study, shrimp shell waste was used directly as an adsorbent on Cu metal, without changing the shrimp shells to chitin or chitosan. Shrimp shell waste at the initial stage was treated including washing, drying, refining, sieving and being activated using 0.5 M HCl solution. The activated shrimp shell powder was then used as an adsorbent against Cu metal, by varying the temperature (30, 40 and 50 oC) and mass of the adsorbent (2,5 ; 5,0 and 7,5 grams) . The maximum adsorption capacity occurs at a temperature of 50oC and an adsorbent mass of 7.5 grams with a capacity of 93.59%. The isotherm model of the adsorption process follows the Harkins Jura isotherm model with a R2 value of 0.9891. The kinetics of the adsorption process followed the pseudo second order kinetics with an adsorption rate constant of 0.019 and an R2 value of 0.9974. The adsorption heat capacity (ΔH) is 7.90 kJ / mol and is endothermic.Key words: adsorption, activation, shrimp shell waste, Cu metal.